Generative AI’s Disruption on Intellectual Property Landscape in Brazil: A Sociotechnical and McLuhan tetrad Analysis - Araújo, Allysson Allex; Kalinowski, Marcos; Pereira Júnior, Elias; Tomaz, Emerson B.; Costa, Catarina (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Generative AI (GenAI) introduces transformative challenges and opportunities to Intellectual Property (IP) processes in countries like Brazil, where existing laws, such as Copyright and IP Laws, do not explicitly account for AI-generated nuances. This paper explores the emerging idea behind GenAI’s impact and disruptive potential on the current Brazilian IP landscape. Using a qualitative approach, we apply McLuhan’s tetrad analysis, informed by Sociotechnical Theory, to identify potential enhancements, obsolescence, retrievals, and reversals that GenAI can bring to IP management in Brazil. Our contributions include advancing the understanding of the influence of GenAI on IP and offering preliminary insights for stakeholders to address emerging challenges and optimize opportunities in Brazil’s evolving IP scenario.